2018
DOI: 10.1016/j.ajhg.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Calmodulin- and Radial-Spoke-Associated Complex Protein CFAP251 Leads to Immotile Spermatozoa Lacking Mitochondria and Infertility in Men

Abstract: Flagella and motile cilia share a 9 + 2 microtubule-doublet axoneme structure, and asthenozoospermia (reduced spermatozoa motility) is found in 76% of men with primary ciliary dyskinesia (PCD). Nevertheless, causal genetic variants in a conserved axonemal component have been found in cases of isolated asthenozoospermia: 30% of men with multiple morphological anomalies of sperm flagella (MMAF) carry bi-allelic mutations in DNAH1, encoding one of the seven inner-arm dynein heavy chains of the 9 + 2 axoneme. To f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 32 publications
4
56
0
Order By: Relevance
“…The genetic characterization of this phenotype began in 2014 with the identification of DNAH1 (dynein axonemal heavy chain 1) as a major gene implicated in MMAF . After the development and the introduction of high throughput sequencing (HTS) techniques such as whole exome sequencing (WES), deleterious mutations were formally identified in eight additional MMAF genes ( AK7 , ARMC2 , CFAP43 , CFAP44 , CFAP69 , FSIP2 , TTC21A , and WDR66 ) showing the high genetic heterogeneity of this phenotype. Despite these important advances in gene identification, about half of the MMAF cases remain idiopathic without a genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic characterization of this phenotype began in 2014 with the identification of DNAH1 (dynein axonemal heavy chain 1) as a major gene implicated in MMAF . After the development and the introduction of high throughput sequencing (HTS) techniques such as whole exome sequencing (WES), deleterious mutations were formally identified in eight additional MMAF genes ( AK7 , ARMC2 , CFAP43 , CFAP44 , CFAP69 , FSIP2 , TTC21A , and WDR66 ) showing the high genetic heterogeneity of this phenotype. Despite these important advances in gene identification, about half of the MMAF cases remain idiopathic without a genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that the MMAF phenotype is associated with genetic mutations. Previous studies revealed that mutations in DNAH1 (MIM: 603332), DNAH2 (MIM: 603333), AKAP4 (MIM: 300185), CCDC39 (MIM: 613798), AK7 (MIM: 615364), CFAP251 (MIM: 618146), CEP135 (MIM: 611423), FSIP2 (MIM: 615796), ARMC2 (MIM: 611226), QRICH2 (MIM: 618304), SPEF2 (MIM: 610172), CFAP69 (MIM: 617949), CFAP43 (MIM: 617558) and CFAP44 (MIM:617559) could cause the human MMAF phenotype . However, more research is needed to reveal the etiology of the remaining 30%–40% of MMAF cases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that loss‐of‐function mutations in several cilia‐ and flagella‐associated protein‐(CFAP)‐encoding genes are identified to cause MMAF in human and mouse . In this study, a homozygous nonsense mutation in another CFAP‐encoding gene, CFAP65 , was detected in a MMAF patient.…”
Section: Discussionmentioning
confidence: 81%
“…Since 2014, when MMAF was defined, studies have shown that mutations in genes associated with sperm flagellum development may lead to MMAF . Here, another candidate gene, CFAP65 , was identified in an infertile male with MMAF by WES.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation